2014
DOI: 10.1016/j.jobaz.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of mefloquine against Schistosoma mansoni infection by prohibition of hepatic oxidative stress in mice

Abstract: The present study was designed to assess the relationship between anti-schistosomal effect of the antimalarial drug mefloquine (Mef) and the oxidative stress status of Schistosoma mansoni infected mice. Forty mice were divided into eight groups (5 mice/group); control (I, II), infected (III, IV), Mef low dosage (200 mg/kg) (V, VI), and Mef high dosage (400 mg/kg) (VII, VIII). Mef (200 and 400 mg/kg) was administered orally as a single dose at days 14 and 35 post infection (PI). All mice were sacrificed after 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…Determination of liver enzyme function, reflected by serum AST and ALT levels, is commonly used to assess the liver damage caused by schistosomal infection [39]. These enzymes are important markers of hepatocellular damage as affirmed by Al-Olayan et al [32].…”
Section: Discussionmentioning
confidence: 99%
“…Determination of liver enzyme function, reflected by serum AST and ALT levels, is commonly used to assess the liver damage caused by schistosomal infection [39]. These enzymes are important markers of hepatocellular damage as affirmed by Al-Olayan et al [32].…”
Section: Discussionmentioning
confidence: 99%
“…Mahmoud and Elbessoumy (2013) concluded that schistosomiasis induced a significant decrease in GSH level in mice liver, thus serving to decrease the hepatic antioxidant capacity and generating lipid peroxides that may in turn play a central role in the pathology associated with schistosomiasis (Fahmy et al, 2014). Moreover, Gharib et al (1999) attributed the decreased GSH level to the increased cytotoxicity with H 2 O 2 which is produced as a result of inhibition of glutathione reductase that keeps GSH in its reduced form.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical burn causes the formation of free radicals, which in turn provokes angiogenesis. Mefloquine, which is an antioxidant and free radical scavenger, protects the endothelium from oxidative stress independent of anti-angiogenic activity [22]. So, these could be the apparent mechanisms of mefloquine in the prevention of proliferation and thus the associated angiogenesis.…”
Section: Discussionmentioning
confidence: 99%